2017
DOI: 10.7717/peerj.3128
|View full text |Cite
|
Sign up to set email alerts
|

Membrane and luminal proteins reach the apicoplast by different trafficking pathways in the malaria parasitePlasmodium falciparum

Abstract: The secretory pathway in Plasmodium falciparum has evolved to transport proteins to the host cell membrane and to an endosymbiotic organelle, the apicoplast. The latter can occur via the ER or the ER-Golgi route. Here, we study these three routes using proteins Erythrocyte Membrane Protein-1 (PfEMP1), Acyl Carrier Protein (ACP) and glutathione peroxidase-like thioredoxin peroxidase (PfTPxGl) and inhibitors of vesicular transport. As expected, the G protein-dependent vesicular fusion inhibitor AlF4− and microtu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The majority of apicoplast resident proteins are encoded in the nuclear genome and are targeted through the endoplasmic reticulum (ER) to the apicoplast via a bipartite N-terminal targeting signal ( 37 ). In contrast, nuclear-encoded transmembrane proteins resident in the apicoplast traffic through the Golgi apparatus ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of apicoplast resident proteins are encoded in the nuclear genome and are targeted through the endoplasmic reticulum (ER) to the apicoplast via a bipartite N-terminal targeting signal ( 37 ). In contrast, nuclear-encoded transmembrane proteins resident in the apicoplast traffic through the Golgi apparatus ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that the Golgi pathway is involved in NEAT protein trafficking ( 38 , 39 ). Therefore, we investigated the effect of TgTrs85 and TgGS27 depletion on apicoplast-targeted trafficking by examining the localization of TgCPN60-3Myc, TgACP-3Myc, TgFtsH1-3V5, and TgAPT1-3V5 or TgATrx1-3Myc.…”
Section: Resultsmentioning
confidence: 99%
“…gondii and a related apicomplexan parasite, P. falciparum (Waller et al, 2000;DeRocher et al, 2005;Chaudhari, Narayan & Patankar, 2012;Heiny et al, 2014;Chaudhari et al, 2017), with some proteins using a Golgi-dependent pathway and others using a Golgi-independent pathway. The determinants on each protein that determine the choice between these pathways are unclear and even more confusingly, in the case of P. falciparum ACP, two studies report opposite results, with one showing a Golgi-dependent pathway (Heiny et al, 2014) and the other showing a Golgi-independent pathway .…”
Section: Discussionmentioning
confidence: 99%
“…TgAPT1 and TgFtsH1, which are membrane proteins with cytosolic C-termini, could not be tested due to the technical constraints of using an HDEL sequence. Further evidence for the ER-apicoplast vesicles being distinct from secretory vesicles lies in a study in P. falciparum that showed, using chemical inhibition of G-protein coupled vesicular transport, that these vesicles were not affected by treatment and are different from the vesicles going to the Golgi (Chaudhari et al, 2017). Isolation and characterisation of the protein and lipid repertoire of these large vesicles would shed light on mechanisms of ER-apicoplast transport in T. gondii.…”
Section: Apicoplast Proteins Are Trafficked To the Apicoplast Indepenmentioning
confidence: 99%